Implementasi Algoritma C4.5 Mengetahui Penyebab Perceraian Dalam Pernikahan (Studi Kasus: Pengadilan Agama Medan Kelas I-A) - Wulan Juni Andari; Efori Buulolo (STMIK Budi Darma, 2020)
Divorce is one act that is hated by Allah. But it is permissible if a husband and wife cannot live together again, when both parties have fulfilled a deadlock in reconciling it will end with a decision that is divorced. Data mining is an automatic analysis of large or complex amounts of data with the aim of determining important patterns or trends. Data mining processing to classify the causes of marriage divorce using C4.5 algorithm by collecting data and classifying data using tree structure representation where each node represents the value of the attribute, the branch represents the value of the attribute and the leaf represents nodes that can search history data for classifying the causes of divorce based on previous traits, so that rules are found that are interconnected with each other. The tools used are Weka (The Waikato Environment for Knowledge Analysis) which is an open source application, Weka has 4 menu tools that can be used, including explorer, experimenter, Knowledgeflow and simple CLI. It has the advantage of many data mining and machine learning algorithms, the results of which are used to predict a set of data